(untitled) (Cuidado y Ocupación Humana, 2023)
Eating habits are a series of behaviors and attitudes that a person has when eating, which should have the minimum nutrient requirements that provide the body with enough energy for the development of daily activities. Night work shifts are related to health problems and disturbances in eating habits, which leads to a greater risk of suffering from states of excess weight and chronic non-communicable diseases, these schedule changes have modified lifestyles and eating habits . Therefore, through an investigation under a quantitative approach, of statistical analysis, with a descriptive and cross-sectional design, they were collected to identify and describe situations, events that would allow the establishment of specific behavior patterns of the eating patterns of health personnel who work in emergencies. during the night shift at a university hospital; where it was possible to conclude that the current intake of hypercaloric foods at after hours is one of the factors with the greatest influence on health, and that these eating patterns managed by health personnel, specifically those who work at night, are usually the most affected due to their high intake of sugars, carbohydrates, saturated fats, etc.; reflecting high rates of obesity, problems related to increased levels of cholesterol, glycemia, triglycerides, which potentially lead to cardiovascular system conditions.